5x-(3x+x)=2(2x+5)

Simple and best practice solution for 5x-(3x+x)=2(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(3x+x)=2(2x+5) equation:


Simplifying
5x + -1(3x + x) = 2(2x + 5)

Combine like terms: 3x + x = 4x
5x + -1(4x) = 2(2x + 5)

Remove parenthesis around (4x)
5x + -1 * 4x = 2(2x + 5)

Multiply -1 * 4
5x + -4x = 2(2x + 5)

Combine like terms: 5x + -4x = 1x
1x = 2(2x + 5)

Reorder the terms:
1x = 2(5 + 2x)
1x = (5 * 2 + 2x * 2)
1x = (10 + 4x)

Solving
1x = 10 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
1x + -4x = 10 + 4x + -4x

Combine like terms: 1x + -4x = -3x
-3x = 10 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3x = 10 + 0
-3x = 10

Divide each side by '-3'.
x = -3.333333333

Simplifying
x = -3.333333333

See similar equations:

| 19-1x=14 | | 34.9+y=13 | | 5a^5+20a^3-40a-25= | | 8+2x=21 | | 3(x+2.84)=2x | | 9+(x-4)=15 | | -7/963x | | x^2+0.755x-0.177=0 | | 9y=8(y+8) | | -1.6(2y+15)=-1.3(2y-10) | | 3(y-2)/5=-2y | | 2(x+4)-4= | | 7(7c-8)=41 | | 4x-8=35 | | 3(4x-8)=0.2(35x+30) | | 3(2x-5+31)=14 | | 1/4y7 | | 5x+6=5(x-9) | | x/3-(3x-7)/5=(x-2)/6 | | 3.2+x=3.4 | | 60/400 | | (56x^2-8x^3)/(x^2(7-x)) | | 5m+1=m^2-49 | | -2(5)+y=1 | | f(x)=2x^2-8x-10 | | 18=k(28) | | 140=30+5s | | 19=a-5.4 | | 3x^2+20x=-12 | | 16=2w+(-8)+10w-12 | | 9(12)+9(3)= | | 50+10x=15+15x |

Equations solver categories